Achieving Psychological Well-Being Through Istighfar Therapy - Sakdiah , Halimatus; Adawiah, Rabiatul; Ariani, Anita (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2024)
Problems are a common thing that occurs in a person’s life. However, not everyone can face it positively, giving rise to restlessness, worry, sadness which disrupts their psychological well-being. Islam teaches that one way to deal with life’s problems is to make istighfar. This research aims to explain the effect of istighfar therapy on psychological well-being. The istighfar therapy applied is istighfar taught by KH. Zaini Bin Abdul Gani (Guru Ijai Sekumpul) which is practiced to overcome negative psychological conditions such as deep sadness, anxiety due to serious problems faced. The research was carried out using literature methods and case studies on subject X with a qualitative approach. The results of the research show that istighfar therapy can help subjects to remember and get closer to Allah, absorb what has happened, admit their weaknesses, surrender, and hope only in Allah, so that it can give rise to feelings of more relaxation, calm , comfort and happiness as the decrease occurs, the psychological burden of the problem faced. In this way, istighfar therapy can provide positive psychological well-being for those who practice it.